PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERORIENTASI PADA PENDEKATAN REALISTICS MATHEMATICS EDUCATION (RME) SUB POKOK BAHASAN BILANGAN PECAHAN SISWA KELAS VII SMP - Indriyani, Desi; Suharto, S; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2012)
Abstract. This study aims to determine the process and the result of the study in terms of fractions with RME approach for seventh grade students. This research is research development using modified Thiagarajan, Semmel and Semmel Model. The device developed is learning the lesson plans, student books, student worksheets, and test questions. The subjects were 38 students of class VII D SMP Negeri 14 Jember. The results showed that the learning has been completed criterian effect, is characterized by the fact haigty learned the value of validity. The device also completed practical learning criterian, the fact is characterized by teachers' activities. The device has also been profen effective learning of a percent highty student activity, student achievement master criteria greater than or equal to 80% classical and 75% of students gave positive reactions to this learning. Key Words : Development of Learning Devices, Realistics Mathematics Education.